2010
DOI: 10.1063/1.3527088
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of InGaN-based laser diodes analyzed by means of electrical and optical measurements

Abstract: In this paper we present a detailed analysis of the degradation of InGaN-based laser diodes carried out by means of electrical and optical techniques. The study is based on the comparison between the degradation kinetics of laser diodes and light-emitting diode LED-like samples, i.e., devices with the same epitaxial structure as the lasers, but with no ridge and facets. Results described in the following indicate that degradation of lasers and LED-like samples is due to the same mechanism, possibly involving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…It was found that in blue MQW GaN/InGaN LEDs with degradation times from some minutes to some 10 h two degradation mechanisms were prevalent: (1) the formation of dislocation bunches in the (0 0 0 1) plane (and associated increase in non-radiative recombination), and (2) increased nonuniformity of injection in p-n junctions [374]. For MOCVD LDs and LEDs perhaps the most insightful studies were reported in papers [370,372]. The authors performed measurements of degradation parameters in MQW LDs and LED-like structures, both prepared on the same epitaxial wafers and differing by the presence of the ridge and mirror facets in lasers (absent in LED structures).…”
Section: V2leds Degradation Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…It was found that in blue MQW GaN/InGaN LEDs with degradation times from some minutes to some 10 h two degradation mechanisms were prevalent: (1) the formation of dislocation bunches in the (0 0 0 1) plane (and associated increase in non-radiative recombination), and (2) increased nonuniformity of injection in p-n junctions [374]. For MOCVD LDs and LEDs perhaps the most insightful studies were reported in papers [370,372]. The authors performed measurements of degradation parameters in MQW LDs and LED-like structures, both prepared on the same epitaxial wafers and differing by the presence of the ridge and mirror facets in lasers (absent in LED structures).…”
Section: V2leds Degradation Studiesmentioning
confidence: 95%
“…Refs. [370][371][372]). For MOCVD-grown LEDs and LDs with low dislocation density grown by ELOG [369] or using low-dislocation density GaN substrates grown by high pressure technique [371] no formation of additional dislocations during degradation was noticed.…”
Section: V2leds Degradation Studiesmentioning
confidence: 97%
“…The first demonstration of emission in GaN-based laser diode was reported in 1996 by Nakamura [139,140]. Still, their maximum optical power, lifetime and reliability are strongly limited by degradation processes induced mainly by increase of the temperature in the particular parts of the laser: facet, active layers or contacts [141][142][143]. Typical degradation mechanisms known from arsenide based devices (like COMD or DLD) are not responsible for failure of GaN based diodes.…”
Section: Gan Based Diode Lasersmentioning
confidence: 99%
“…Common problem of SSL based on semiconductors is their heating [6] [7] [8], when the current increases. It doesn't concern only lighting domain, but also data storage or communication, when coupling of laser and phosphor is used [9] [10].…”
Section: Introductionmentioning
confidence: 99%